Kaotičnost hiperboličnih avtomorfizmov torusa - Lakner, Mitja (Obzornik za matematiko in fiziko, 2015)
In our previous article M. Lakner, P. Petek, M. Škapin Rugelj, Vrnitev Arnoldove mačke, Obzornik mat. fiz. 62 (2015) 41-52 we defined the hyperbolic automorphism of the torus, returning the rastered image in few steps. Here we consider the mapping on the entire torus and find it is chaotic in the sense of Davaney. Beforehand we get acquainted with tha notion of chaoticity and set up a simple example.
Keywords: chaoticity; hiperbolični avtomorfizmi; hyperbolic automorphism; kaotični sistem; mapping on the torus; preslikava na torusu